The Effectiveness of Instructional Scaffolding Strategy in Developing Learners' Attitudes towards the Subject of Chemistry - Seenaa Jabbar Cheykyor - Rawaida Alzein Naaman ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
This study aims to investigate the effectiveness of using the instructional scaffolding strategy in  developing  learners' attitudes towards the subject of chemistry. The study has followed two-group experimental  design. One group, the experimental group, would receive the treatment, the scaffolding strategy. While the other group, the control group, would not receive the treatment, the scaffolding strategy. The sample comprises 60 female students  assigned randomly to the experimental group and the control group. Each group has got 30 female students. The sample has been selected from Al-Shaymaa Intermediate School second-grade students in Maysan province in the academic year 2022-2023. Unit Two " Elements and Compounds" is the material that has been taught for the two groups. An attitude scale towards the subject of chemistry has been applied at the end of the experiment. The results have revealed a statistically significant difference between the mean scores of the experimental group and the control group. The experimental group has a higher level of interest and preference for chemistry than the control group. The researchers have recommended the integration of  the scaffolding strategy in the chemistry curriculum.